Assessment of Quality Characteristics of Boiled Yam Tubers Available in Bangladesh - Jahan, FN; Rahim, MA; Hossain, MM; Rahman, MH; Chowdhury, MAZ; Moniruzzaman, M; Samanta, AK (SAARC Journal of Agriculture, 2020)
Tuber of yam (Dioscorea spp.) is one of the important foods widely popular in several countries. In spite of its assignment in the category of underutilized crop, the tubers of yam are consumed by the people of Bangladesh in different forms. The current paper has made an endeavor to evaluate the sensory qualities of boiled yam tubers by the panel of evaluators. The quality parameters that were considered for evaluation of boiled yam tubers were ease of peeling, poundability, discoloration of water after boiling, color and texture, bitterness, sweetness, etc. Evidently, it was possible to judge the quality of yams based on the sensory evaluation as it is one of the important steps for acceptability of foods and their subsequent usages. Around 31 tuber samples were harvested during the winter season from the Germplasm Centre of Bangladesh Agricultural University. Amongst the 31 samples, 24 came under the category of ‘easy to peel’, and ‘difficult to peel’ were only 7 samples. Regarding the color after cooking, 19 samples were “white, not colored”, whereas, 3 samples were intermediate and 9 samples were highly colored; might be attributed by the presence of phyto-compounds. Nevertheless, two samples i.e. RHMF002 and RMHF010 were found to possess most of the favorable sensory characters in terms of discoloration of water after boiling, sweetness, bitterness, texture, poundability, etc. SAARC J. Agri., 18(1): 173-182 (2020)